2021
DOI: 10.7554/elife.59751
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dorsal horn CGRP-expressing interneurons to mechanical sensitivity

Abstract: Primary sensory neurons are generally considered the only source of dorsal horn calcitonin gene-related peptide (CGRP), a neuropeptide critical to the transmission of pain messages. Using a tamoxifen-inducible CalcaCreER transgenic mouse, here we identified a distinct population of CGRP-expressing excitatory interneurons in lamina III of the spinal cord dorsal horn and trigeminal nucleus caudalis. These interneurons have spine-laden, dorsally-directed, dendrites and ventrally-directed axons. As under resting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…For example, it was recently shown that CGRP is also expressed in a subset of dorsal horn interneurons, and their selective activation or ablation has behavioral consequences (Löken et al , DOI: 10.7554/eLife.59751). 1 The authors could cite these and other relevant literature to strengthen the point for developing this new tool. With the tool in hand, the authors explored the behavioral effects of ablating different subsets of primary sensory neurons and noted some differences.…”
mentioning
confidence: 99%
“…For example, it was recently shown that CGRP is also expressed in a subset of dorsal horn interneurons, and their selective activation or ablation has behavioral consequences (Löken et al , DOI: 10.7554/eLife.59751). 1 The authors could cite these and other relevant literature to strengthen the point for developing this new tool. With the tool in hand, the authors explored the behavioral effects of ablating different subsets of primary sensory neurons and noted some differences.…”
mentioning
confidence: 99%
“…We found that compared with the vehicle-treated mice, the paw thermal withdrawal latency (PTWL) of T1DM mice dropped after STZ injection ( Figure 1(b) ; T1DM vs. control, F (1, 14) = 155.7, P < 0.0001, n = 8), indicating the occurrence of thermal hypersensitivity in T1DM mice. CGRP is a neuropeptide widely distributed in nociceptive circuits and is closely involved in pain transmission [ 41 ]. The immunostaining of the SDH suggested that the CGRP immunoreactivity of T1DM mice was more intense than that of control mice ( Figure 1(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have identified that loss of Lbx1 leads to improper patterning of dorsal horn neurons and disrupted sensory afferent innervation 62,63 . Furthermore, Lbx1 has been utilized in intersectional approaches to target neurons implicated in mechanical hypersensitivity 64 , pain 65,66 and itch 28,67 . To further understand Lbx1 , we developed a method to target Lbx1 -lineage neurons in the adult.…”
Section: Resultsmentioning
confidence: 99%